Microanatomical Studies on the Relationship Between Exocrine and Endocrine Components of Pancreas in Crossbred Goats During Prenatal and Postnatal Development - Sreeranjini, A.R. (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on the pancreas of goat foetuses from second to fifth month of prenatal life and male kids up to six months of age. Tissue samples were fixed in 10 per cent neutral buffered formalin and were processed for paraffin embedding. Sections were stained by routine and special stains for histological studies.Immunohistochemistry was performed as per the methodology of Santa Cruz Biotechnology(Inc.). Transmission electron microscopywas done at Ruska labs, Hyderabad. Immunohistochemical studies on the pancreatic primordium in the second month of prenatal period showed that the development of endocrine component was initiated by budding of cells from the ductules in the primordium. By third month of prenatal life, fully formed islets were observed but some of them retained their contact with the tubules. The pancreatic primordia fused and the number of ductules increased. These ductules showed extensive branching as well as elongation and branches of ductules showed the formation of acini at their ends. In the pancreas of postnatal animals,someislet cells were in direct contact with the acinar cells. Electron microscopic studies revealed the presence of intermediate cells interspersed with acinar cells in exocrine acini. A few islets were seenabutting the intralobular as well as interlobular ducts. These structural relations indicatedthat exocrine and endocrine compartments of pancreas might not be independent compartments and some kind of regulatory mechanism could exist betweenthem.